Deep Generative Models of LDLR Protein Structure to Predict Variant Pathogenicity - James, Jose K.; Norland, Kristjan; Johar, Angad S.; Kullo, Iftikhar J. (Journal of lipid research, 2023)
The complex structure and function of low-density lipoprotein receptor (LDLR) makes classification of protein-coding missense variants challenging. Deep generative models, including evolutionary model of variant effect (EVE), evolutionary scale modeling (ESM), and AlphaFold 2 (AF2), have enabled significant progress in the prediction of protein structure and function. ESM and EVE directly estimate the likelihood of a variant sequence but are purely data-driven and challenging to interpret. AF2 predicts LDLR structures but variant effects are explicitly modeled by estimating changes in stability. We tested the effectiveness of these models for predicting variant pathogenicity compared to established methods. AF2 produced two distinct conformations based on a novel hinge mechanism. Within ESM’s hidden space, benign and pathogenic variants had different distributions. In EVE these distributions were similar. EVE and ESM were comparable to Polyphen-2, SIFT, REVEL and Primate AI for predicting binary classifications in ClinVar. However, they were more strongly correlated with experimental measures of LDL uptake. AF2 poorly performed in these tasks. Using the UK biobank to compare association with clinical phenotypes, ESM and EVE were more strongly associated with serum LDL-C than Polyphen-2. ESM was able to identify variants with more extreme LDL-C levels than EVE and had a significantly stronger association with atherosclerotic cardiovascular disease. In conclusion, AF2 predicted LDLR structures do not accurately model variant pathogenicity. ESM and EVE are competitive with prior scoring methods for prediction based on binary classification in ClinVar but are superior based on correlations with experimental assays and clinical phenotypes.